PENGARUH PENDAPATAN ORANG TUA DAN GAYA PERGAULAN TERHADAP PERILAKU KEUANGAN MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - Wendi Crisdianto Tamba; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to obtain knowledge about the influence of parental income and social style on financial behavior of students of the economic education study program, HKBP Nommensen Pematang Siantar University This type of research is a quantitative research with a quantitative descriptive data analysis approach with the testing medium used is SPSS 22. The total population in this study was 267 people, and the sample used was 160 people The sample collection technique used was simple random sampling. The data collection technique used is a questionnaire (questionnaire). The hypothesis data collection technique uses multiple regression analysis and determination coefficient (R2). obtained a = 17.510, b1 = 0.494, b2 = 0.272 and e = 3.371. Contribution can be determined by squaring the simple influence